Dinámica entre la gestión de riesgos laborales y la productividad en la empresa Holcim Ecuador S.A. – Planta Latacunga. - Totoy Cañizares, Danny Deyvis (2022)
The present work entitled Dynamics between Occupational Risk Management and Productivity in the Holcim Ecuador S.A. Company. – Latacunga Plant, aimed to theoretically describe occupational risk management and its dynamics with productivity in the industrial sector, productivity and its organizational dynamics; carry out a situational analysis on the management of labor risks and productivity developed within the company; and propose occupational risk management strategies that boost organizational productivity. The applied methodology was descriptive, through the application of a survey addressed to 35 workers of the company; From the results of the survey, the situational analysis was obtained around the Management of Occupational Risks and Productivity. Subsequently, six strategies were generated, which are: workplace safety, zero harm culture, system and processes, health risk control, reducing road fatalities and environmental excellence; These focus areas stimulate these two thematic axes of the research with an investment amounting to USD 200,000, an amount fully accessible to the company during this period until 2025.